Unconventional plants for food purposes sold at the fairs in São Luís, Maranhão, Brazil - Marques, Georgiana Eurides de Carvalho (2021)
The research analyzed the production, commercialization and consumption of unconventional food plants (PANC) at fairs in São Luís (MA) and the chemical composition of the species Hibiscus sabdariffa L. (vinagreira) and Talinum paniculatum (Jacq.) Gaertn (joão-gome). Questionnaires were applied to three priority groups: marketers, consumers and producers, asking about their knowledge related to PANC, financial return, benefits, planting and frequency of consumption. The chemical parameters analyzed were protein, lipids, fibers, ashes, Brixº, pH, titratable acidity, vitamin C and reducing sugars following different methodologies. The results showed that in the commercial centers of São Luís, the PANC are commercialized and their benefits to health and income generation are recognized by the marketers, producers and consumers, mainly for the female gender. The main responsible for its planting and commercialization are women and the main consumers are adults and the elderly. In the vinagreira, an acidic flavor determined by high pH, titratable acidity and vitamin C was observed. The joão-gome showed little flavor, high content of Vitamin C, protein and fibers. The high protein and fiber content in both species shows the nutritional richness characteristic of PANC. Therefore, the chemical parameters of both species demonstrated the nutritional potential of these plants, justifying their wide use in cooking and traditional medicine in the region.